Kajian Kriminologi Terhadap Pencurian Yang Dilakukan Oleh Prajurit TNI Di Wilayah Hukum Pengadilan Militer III-15 Kupang (Studi Kasus Putusan Nomor: 35-K/PM.III-15/AU/XII/2022) - Saramita Huwae; Rudepel Petrus Leo; Debi F. Ng. Fallo (Shofanah Media Berkah, 2023)
Cases of theft are a taboo matter and do not only occur in society, but have also spread to the state apparatus, especially within the TNI, where they can commit the crime of theft. The crime of theft committed by members of the TNI is a very complex problem and must be firmly eradicated. The problem formulation in this research is: (1) What are the factors that cause TNI Soldiers to commit theft? (2) What are the efforts to deal with theft committed by TNI Soldiers in the jurisdiction of Military Court III-15 Kupang? This research aims to determine the causal factors and efforts to overcome theft by TNI soldiers. This research is empirical juridical research. The method used in collecting data is interviews with three respondents and document study which is then analyzed and then presented and explained in a qualitative descriptive manner. The results of this research show: (1) There are two factors that cause TNI Soldiers to commit theft, namely, internal factors in the form of intention factors and external factors in the form of opportunity factors, environmental factors and economic factors (2) Efforts made to overcome theft are preemptive efforts, efforts preventive and repressive efforts. Countermeasures against theft committed by TNI Soldiers in the jurisdiction of the III-15 Kupang Military Court, in the form of law enforcement by imposing sanctions and instilling moral values ​​and doing positive things to prevent theft from occurring.